Effects of the Informed Health Choices podcast on the ability of parents of primary school children in Uganda to assess claims about treatment effects: a randomised controlled trial. Issue 10092 (22nd July 2017) - Semakula, Daniel; Nsangi, Allen; Oxman, Andrew D; Oxman, Matt; Austvoll-Dahlgren, Astrid; Rosenbaum, Sarah; Morelli, Angela; Glenton, Claire; Lewin, Simon; Kaseje, Margaret; Chalmers, Iain; Fretheim, Atle; et al.
Summary: Background: As part of the Informed Health Choices project, we developed a podcast called The Health Choices Programme to help improve the ability of people to assess claims about the benefits and harms of treatments. We aimed to evaluate the effects of the podcast on the ability of parents of primary school children in Uganda to assess claims about the effects of treatments. Methods: We did this randomised controlled trial in central Uganda. We recruited parents of children aged 10–12 years who were in their fifth year of school at 35 schools that were participating in a linked trial of the Informed Health Choices primary school resources. The parents were randomly allocated (1:1), via a web-based random number generator with block sizes of four and six, to listen to either the Informed Health Choices podcast (intervention group) or typical public service announcements about health issues (control group). Randomisation was stratified by parents' highest level of formal education attained (primary school, secondary school, or tertiary education) and the allocation of their children's school in the trial of the primary school resources (intervention vs control). The primary outcome, measured after listening to the entire podcast, was the mean score and the proportion of parents with passing scores on a test with two multiple choice questions for each of nine key concepts essential to assessing claims about treatments (18 questions in total). We did intention-to-treat analyses. This trial is registered with the Pan African Clinical Trial Registry, number PACTR201606001676150. Findings: We recruited parents between July 21, 2016, and Oct 7, 2016. We randomly assigned 675 parents to the podcast group (n=334) or the public service announcement group (n=341); 561 (83%) participants completed follow-up. The mean score for parents in the podcast group was 67·8% (SD 19·6) compared with 52·4% (17·6) in the control group (adjusted mean difference 15·5%, 95% CI 12·5–18·6; p<0·0001). In the podcast group, 203 (71%) of 288 parents had a predetermined passing score (≥11 of 18 correct answers) compared with 103 (38%) of 273 parents in the control group (adjusted difference 34%, 95% CI 26–41; p<0·0001). No adverse events were reported. Interpretation: Listening to the Informed Health Choices podcast led to a large improvement in the ability of parents to assess claims about the effects of treatments. Future studies should assess the long-term effects of use of the podcast, the effects on actual health choices and outcomes, and how transferable our findings are to other countries. Funding: Research Council of Norway.